2018
DOI: 10.1128/jvi.00084-18
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of N-Linked Glycosylation in Pseudorabies Virus Glycoprotein gH

Abstract: Many viral envelope proteins are modified by asparagine (N)-linked glycosylation, which can influence their structure, physicochemical properties, intracellular transport, and function. Here, we systematically analyzed the functional relevance of N-linked glycans in the alphaherpesvirus pseudorabies virus (PrV) glycoprotein H (gH), which is an essential component of the conserved core herpesvirus fusion machinery. Upon gD-mediated receptor binding, the heterodimeric complex of gH and gL activates gB to mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
(124 reference statements)
1
9
0
Order By: Relevance
“…We demonstrate that the individual N-glycosylation sites play a modulatory but dispensable role for gB function, whereas simultaneous inactivation of all sites severely affects gB function in fusion, highlighting an important role of these glycans for correct folding, structure and/or stability of gB. Although mutation of most of the sites had no notable effect on gB processing and function during in vitro fusion and entry, which is largely congruent to our results on the role of N-glycans on PrV gH [30], we found that N-glycosylation of PrV gB at the highly conserved positions N154 and N700 is important for proper processing of gB by cellular furin. Taken together, this study expands our knowledge on the role of N-linked glycans on the herpesvirus fusion protein gB.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We demonstrate that the individual N-glycosylation sites play a modulatory but dispensable role for gB function, whereas simultaneous inactivation of all sites severely affects gB function in fusion, highlighting an important role of these glycans for correct folding, structure and/or stability of gB. Although mutation of most of the sites had no notable effect on gB processing and function during in vitro fusion and entry, which is largely congruent to our results on the role of N-glycans on PrV gH [30], we found that N-glycosylation of PrV gB at the highly conserved positions N154 and N700 is important for proper processing of gB by cellular furin. Taken together, this study expands our knowledge on the role of N-linked glycans on the herpesvirus fusion protein gB.…”
Section: Discussionsupporting
confidence: 88%
“…Host-cell-derived N-linked glycans on viral envelope proteins can influence protein folding and stability, transport, viral entry and spread, and immune evasion [ 49 ]. Recently, we investigated the functional relevance of N-linked glycosylation in PrV gH [ 30 ]. In the present study, we extended our analyses to N-linked glycans on PrV gB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sows infected with PRV show clinical symptoms of abortion, and infected newborn piglets have severe neurological symptoms, with morbidity and mortality near 100% for those younger than 2 weeks old. PRV mutant strains also cause severe respiratory symptoms in adult pigs, and cause reproductive failure in boar [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%